EVALUATION OF UNIVERSITY WEBSITES TARGETING ENGLISH SPEAKING USERS: A COMPARATIVE ANALYSIS OF SELECTED SITES IN DEVELOPED AND DEVELOPING COUNTRIES - Ongus, R.W.; Kemparaju, T. D.; Nyamboga, C.M. (Malaysian Journal of Library and Information Science, 2006)
The rapid development and increasingly popular usage of the Internet through the World Wide Web (WWW) have offered information professionals a very lucrative opportunity to assert themselves as information gatekeepers and gateways. Through systematic evaluation procedures on information resources such as websites, proper guidance may be offered to targeted end users in order to facilitate much more efficient retrieval of information and hopefully, better utilization of the same. This paper looks at several selected university websites designed in English, all of which were subjected to a uniform set of criteria for the purposes of evaluating the website design and content coverage. Following its classification into developing and developed countries of origin, the data collected was comparatively analysed and subsequent inferences together with recommendations proffered in line with the set objectives.